Modelling Oil Palm's Sustainable Management and Practices: A Framework Based On Economic Principles - Aikanathan, S.; Sasekumar, A.; Chenayah, S.; Basiron, Y.; Sundram, K. (Malaysian Palm Oil Council (MPOC), 2014)
In recent years, sustainability has emerged as a focal area of cross-disciplinary inquiry and has tended to be problem-driven. These developments are supported by a number of economic theories that include the Neo- Malthusian theory, Kuznet’s Hypothesis and Hardin’s Tragedy of the Commons. Two frameworks: theoretical and conceptual were created by assessing correlations based on the above mentioned economic theories. Study frameworks were designed and validated as “economy tools’ for quantitative analysis of variables that are deemed important for sustainable management. These frameworks were applied to the palm oil industry and its sustainability challenges. Stakeholders’ perceptions and their management were incorporated in the overall palm oil economic analysis for sustainability management.